2014
DOI: 10.1111/jbfa.12078
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Networks and Earnings Informativeness: Evidence from Corruption Cases

Abstract: The measurement difficulties arising from relationship‐based business transactions can result in accounting opacity. We test this hypothesis by exploiting a natural experiment. Using a sample of firms that were networked with 45 high‐level Chinese bureaucrats involved in corruption scandals between 1996 and 2007, we examine the patterns in the earnings informativeness of these firms before and after the exogenous break of the networks. We predict that the costs and benefits of business‐politics relationships, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
2
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 83 publications
(127 reference statements)
1
32
2
3
Order By: Relevance
“…10. Using other settings and relatively small samples, Batta et al (2014), Chi et al (2016), and Fan et al (2014) find either the opposite of what we find or no effects, thus providing further tension to our hypothesis. Similar to Chaney et al (2011), these studies do not employ as strict a research design as we do in this paper.…”
contrasting
confidence: 79%
“…10. Using other settings and relatively small samples, Batta et al (2014), Chi et al (2016), and Fan et al (2014) find either the opposite of what we find or no effects, thus providing further tension to our hypothesis. Similar to Chaney et al (2011), these studies do not employ as strict a research design as we do in this paper.…”
contrasting
confidence: 79%
“…Gompers, Ishii, and Metrick (2003) argues that ownership structure affects the frequency with which stocks trade. Different types of ownership have an impact on stock price informativeness including ownership concentration (Fan, Guan, Li, & Yang, 2014); government ownership (Ben‐Nasr & Cosset, 2014); block holdings (Brockman & Yan, 2009) and institutional investors (Boehmer & Kelley, 2009). Thus, the impact of trading frequency (liquidity) measures on earnings informativeness in our sample may be explained by differences in ownership structure.…”
Section: Discussionmentioning
confidence: 99%
“…First, the lower the corruption in a country the higher the levels of compliance and increase in compliance levels with goodwill disclosures over time. Prior literature indicates that high levels of corruption are associated with a low quality of accounting (c.f., Fan et al, 2014), as manifested in less transparent financial statements (c.f., Kimbro, 2002;DiRienzo, 2007;Houqe and Monem, 2016) and earnings opacity (c.f., Picur, 2004;Riahi-Belkaoui, 2004). Thus, our findings extend this strand of the accounting literature by showing that corruption is also related to compliance levels and change in these levels with mandatory accounting disclosures, in particular with goodwill related disclosures which are sensitive and associated with proprietary information.…”
Section: Discussion Of Empirical Findings In Relation To H1 -H4mentioning
confidence: 99%
“…Similarly, Riahi-Belkaoui, (2004, p. 82), using a cross-country longitudinal dataset covering the period 1985 to 1998 observed that "corruption creates a climate conducive to a low quality accounting" and finds that earnings opacity is positively related to the presence of corruption in a given country. Furthermore, Fan et al (2014) highlight the link of accounting opacity and corruption in China, whereby managers distort accounting information to cover their expropriation of interests from common investors. Recently, Lourenço et al, (2017) who utilise data from 33 countries worldwide find that country perceived corruption is related to higher incentives for firms to manipulate earnings in the case of emerging countries.…”
Section: Corruption Accounting Disclosure and Compliancementioning
confidence: 99%